2018
DOI: 10.1039/c8lc01109e
|View full text |Cite
|
Sign up to set email alerts
|

Disposable silicon-glass microfluidic devices: precise, robust and cheap

Abstract: We developed a method for reducing the cost of Si-glass microfluidic chips while maintaining the precision and robustness unique to Si-glass system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…Silicon-based devices have also been used and have many of the same benefits as glass. ,, Silicon, however, is not optically clear, and thus a portion of the device must be nonsilicon for in situ imaging. Additionally, silicon has been widely used in the fabrication of electronics, and techniques for fabricating silicon-based platforms, including dry or wet etching, laser-drilling, sand-blasting, and direct, anodic, or adhesive bonding, are well established .…”
Section: Pdms Alternatives For Device Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon-based devices have also been used and have many of the same benefits as glass. ,, Silicon, however, is not optically clear, and thus a portion of the device must be nonsilicon for in situ imaging. Additionally, silicon has been widely used in the fabrication of electronics, and techniques for fabricating silicon-based platforms, including dry or wet etching, laser-drilling, sand-blasting, and direct, anodic, or adhesive bonding, are well established .…”
Section: Pdms Alternatives For Device Fabricationmentioning
confidence: 99%
“…Additionally, silicon has been widely used in the fabrication of electronics, and techniques for fabricating silicon-based platforms, including dry or wet etching, laser-drilling, sand-blasting, and direct, anodic, or adhesive bonding, are well established . Silicon-glass microfluidic devices have been reported that are disposable, inexpensive (close to $5 USD), and can be rapidly fabricated for high-throughput experiments to address the main disadvantages of glass; however, such combined silicon-glass devices have yet to be widely utilized within MPS applications.…”
Section: Pdms Alternatives For Device Fabricationmentioning
confidence: 99%
“…These two PLL-ZID macromolecules were first synthesized and characterized in solution (by techniques including NMR, DOSY and IR) prior to surface immobilization. In this study, silicon oxide was used as a model substrate because of its relevance in, e.g., biosensors [46] and microfluidic devices [47]. After self-assembly on silicon oxide surfaces, the formed coatings were investigated using water contact angle (WCA) measurements and X-ray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, silicon oxide was used as a model substrate because of its relevance in, e.g., biosensors 44 and microfluidic devices. 45 We explored three different routes toward such a coating with varying degrees of grafting-to and grafting-from components ( Figure 1 ). Route A: a coating was completely grafted from the surface.…”
Section: Introductionmentioning
confidence: 99%